Defense mechanism and narcissistic behavior: A Study of R.F. Kuang’s Yellowface - Marfinda, Shaga; Istiani, Imas (Universitas Muhammadiyah Purwokerto, 2026)
This study examines the defense mechanisms and narcissistic behavior of the main character in R. F. Kuang’s novel Yellowface (2023) using Karen Horney’s concepts of the idealized self and neurotic needs, as well as Christopher Lasch’s ideas about cultural narcissism. This research explores how June protects herself from envy and guilt by using various forms of self-deception. It also explores how the social media-driven publishing world shapes June’s narcissistic behavior. This research uses qualitative-descriptive methods and deep text analysis. The focus of the study is on the emotional insecurity, the need for recognition, and the dependence on public opinion. Findings show that June creates an idealized image of herself as a successful writer and maintains it through self-deception. At the same time, the publishing industry that focuses on visibility, approval, and performance affects her by pushing her to judge herself and her value through attention and compliments. When this recognition is lost, she feels anxiety, fear, and emotional instability. This study suggests that self-deception and narcissistic behavior in Yellowface are not just personal weaknesses, but psychological strategies created by internal conflict and a competitive cultural environment.